Relationship between Marketing Mix and Cunsomers’ Loyalty of Hatten Wines Products - Citra Dewi, Ida Ayu Putu; Suryawardani, I Gusti Ayu Oka (E-Journal of Tourism; Volume 6 Number 1 (March 2019)DO - 10.24922/eot.v6i1.47982, 2019)
Hatten Wines is one of the alcoholic beverage products produced in Bali and owned by Balinese. Its role is very important as a substitute product for imported alcoholic beverage products. The research objectives are: (i) identifying the marketing mix variables that determine the purchasing decisions and loyalty to Hatten Wines products and their forming indicators, and (ii) investigating the roles of marketing mix on the customers' purchasing decisions and loyalty to Hatten Wines products. The study was conducted in Sanur, Kuta and Nusa Dua by distributing questionnaires to 100 foreign tourists. The data was analyzed based on the factor analysis by using SPSS program. The results of the study indicate that; (i) Marketing Mix variables that determine the purchasing decisions and product loyalty to Hatten Wines consist of products, prices, promotions, places and distribution. Product variables are formed from five indicators, namely brand, taste, packaging, aroma, and product variety. Price variables are formed from three indicators, namely affordability of prices, value for money, and price competitiveness. Promotion variables are formed from four indicators, namely promotion services, media promotion, promotion quality, and promotion quantity. Place and distribution variables are formed from three indicators, namely place of sale, product availability, and ease of access. (ii) Hatten Wines Marketing Mix plays a positive role and is significantly related to the consumers' purchasing decisions and loyalty in consuming Hatten Wines, which is 60.946%. The remaining 39.054% is influenced by other variables not included in the model. Keywords: marketing mix, consumers’ loyalty, Hatten Wines, Bali.